Penerapan Internet Financial Reporting (IFR) Pada Bank Umum Syariah Di Indonesia - Ria Nur Rizqiah; Ahmad Tarmizi Lubis (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2017)
Along with the rapid development of internet technology today, the company's financial reporting activities can be done via the Internet in real time in an easy way and a wider scope. Internet-based financial reporting is commonly known as the Internet Financial Reporting (IFR). This research is a descriptive study that aims to determine the implementation of IFR on Islamic Banks in Indonesia. The variables in this study consisted of content, presentation and timeliness variable with a total of 112 items tested indicators. The results of this study indicate that the eleventh BUS sampled research has been able to apply IFR. IFR score obtained by each BUS has a nearly equal value ranging from 49% to 63% with the total maximum score of 100% and average score of 55%